The Effect of Trust, Income, and Life Style on Fashion Purchase Decisions Using Paylater Among Accounting Students at UPN “Veteran” East Java - Nanda Evita Ramadhani; Sri Trisnaningsih (PT. Maju Malaqbi Makkarana, 2026)
This study aims to examine and analyze the effect of trust, income, and life style on fashion purchase decisions using paylater among Accounting students at UPN “Veteran” East Java. The background of this research is based on the rapid development of financial technology and e-commerce, which has influenced consumer behavior, particularly among university students, including their purchasing decisions for fashion products through paylater services. This phenomenon highlights the importance of understanding the factors that influence consumers’ decisions to use paylater services. This research employs a quantitative approach using primary data collected through a questionnaire distributed via Google Form. The sample consists of 72 respondents selected using a random sampling method. Data analysis was conducted using SPSS to test the relationships between variables. The results show that trust, income, and life style have a positive and significant effect on fashion purchase decisions using paylater. These findings are consistent with the Theory of Planned Behavior (TPB), which states that consumer behavior is influenced by attitudes, subjective norms, and perceived behavioral control.